Peningkatan Pendapatan Petani Penggarap Melalui Sistem Bagi Hasil - akhmad munif mubarok; Anggun Vitasari (Journal of Social and Political Science)
Profit-sharing system is a bond or a cooperation agreement between land owners and their workers as tenants. The wage of cultivation of the land is taken or given from crops which are cultivated. The amount of the profit-sharing is the amount of wages earned by each farmer both landowners and tenants based on an agreement that is 5: 1 on the crop, so that sharecroppers can increase their income and fulfill their family’s needs. Profit-sharing system is done once a year during the paddy season. This is caused by insufficient irrigation water requirements for paddy crops. This research aims to explain and to describe the increase of sharecroppers’ income throughprofit-sharing system in Dawuhan Village Grujugan Subdistrict. This research used a qualitative method. The used informant determination method was purposive while the data collection techniques were through observation, interviews and documentation. The data obtained from the field were analyzed by using data analysis methods. The validity of the data, researcher used a type of triangulation. The results showed that the increase of income of farming community in Dawuhan village could be seen from the changes in socioeconomic conditions. Moreover, it then gave a positive impact to the society of Dawuhan village because the production resultof harvest time could be their savings during waiting of paddy season arrives. There was an interlude in paddy season; it was tobacco and chili seasons. Todays, profit-sharingsystem was still implemented as a tradition or habit that was based on mutual trust and helping each other among the farming community. Keywords: Profit-sharing System, Sharecroppers, and The Increase of Income